2005
DOI: 10.1002/uog.1938
|View full text |Cite
|
Sign up to set email alerts
|

How to identify twins at low risk of spontaneous preterm delivery

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
2
32
1
1
Order By: Relevance
“…The association between a short sonographic cervical length and the risk of subsequent PTB is well-established in singleton 11, 23-28, 52-61 and twin gestations 12, 29-40, 62-64 . Since cervical length changes over time as the time of the onset of labor approaches, we propose that cervical shortening detected with serial sonographic examinations may yield information about the risk of PTB which is not available at the time of the routine sonographic examination in the midtrimester.…”
Section: Commentmentioning
confidence: 99%
“…The association between a short sonographic cervical length and the risk of subsequent PTB is well-established in singleton 11, 23-28, 52-61 and twin gestations 12, 29-40, 62-64 . Since cervical length changes over time as the time of the onset of labor approaches, we propose that cervical shortening detected with serial sonographic examinations may yield information about the risk of PTB which is not available at the time of the routine sonographic examination in the midtrimester.…”
Section: Commentmentioning
confidence: 99%
“…The association between a short sonographic cervical length and the risk of subsequent PTB is well-established in singleton 11, 23-28, 52-61 and twin gestations 12,[29][30][31][32][33][34][35][36][37][38][39][40][62][63][64] . Since cervical length changes over time as the time of the onset of labor approaches, we propose that cervical shortening detected with serial sonographic examinations may yield information about the risk of PTB which is not available at the time of the routine sonographic examination in the midtrimester.…”
Section: Commentmentioning
confidence: 99%
“…This, in turn, has led to the relatively common practice of serial monitoring of CL during the second trimester in women at risk of PTB, including women with twin gestations. [38][39][40][41] However, one question that needs to be answered before such practice becomes accepted into routine care relates to the optimal strategy for the integration and interpretation of the additional information derived from serial measurements of CL. One possible strategy for integrating and interpreting a series of measurements, which is used in the current study, is by classifying them into one of several recognized patterns.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of prospective studies [20][21][22][23][24][25][26][27][28][29][30] have shown the predictive value of midtrimester cervical length measurement in twin pregnancies; these data were collected in two large meta-analyses. The first meta-analysis included 21 studies, 16 in asymptomatic women and only 5 in symptomatic women; the collected data included 3,523 women.…”
Section: Prediction Of Preterm Birthmentioning
confidence: 99%